Variability in the frequency of Single nucleotide polymorphisms of N-acetyl transferase (NAT2) gene in Vietnamese - Long, Dinh Doan; Nhung, Pham Thi Hong; Anh, Tran Thi Thuy; Yen, Hoang Hai (VNU Journal of Science: Natural Sciences and Technology; Vol 27 No 4, 2011)
Abstract . N-acetyltransferase 2 (NAT2) modifies drug toxicity and cancer risk due to its role in bioactivation and detoxification of arylamine and hydrazine drugs and carcinogens. Human NAT2 alleles possess a combination of single nucleotide polymorphisms (SNPs) associated with slow acetylation phenotypes. To identify variations in genetic polymorphisms of drug-metabolizing enzyme in Vietnamese for the first time, three SNPs of NAT2, C341T (I114T), G590A (R197Q) and G857A (G286E) were determined by using PCR- RFLP technique. For NAT2 , the 341T allele appear with a rather low frequency of 2% in our 100 subjects. The frequencies of alleles 590A and 857A were also examined in this study with 12.5% and 25%, respectively. The variation in the genetic polymorphisms of drug-metabolizing enzyme is worthy of futher study to understand different therapeutic and adverse drug responses in Vietnamese population. Keywords :  N-acetyltransferase 2 enzyme, single nucleotide  polymorphism  (SNP), PCR-RFLP.